2006
DOI: 10.1007/s10584-005-9042-x
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Climate Change on Indian Agriculture: A Review

Abstract: During the recent decade, with the growing recognition of the possibility of climate change and clear evidence of observed changes in climate during 20 th century, an increasing emphasis on food security and its regional impacts has come to forefront of the scientific community. In recent times, the crop simulation models have been used extensively to study the impact of climate change on agricultural production and food security. The output provided by the simulation models can be used to make appropriate cro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
99
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 348 publications
(125 citation statements)
references
References 52 publications
4
99
0
Order By: Relevance
“…The northern tropical Indian Ocean and the surrounding lands are the location of a strong monsoon system, which has a profound impact on the socio-economy of one of the most densely populated areas of the world (Saha et al, 1979;Mooley et al, 1981;Mall et al, 2006). During the southwest (summer) monsoon, warm, moist air prevails, and a strong southwesterly wind jet runs diagonally across the Arabian Sea ( Fig.…”
Section: Introductionmentioning
confidence: 99%
“…The northern tropical Indian Ocean and the surrounding lands are the location of a strong monsoon system, which has a profound impact on the socio-economy of one of the most densely populated areas of the world (Saha et al, 1979;Mooley et al, 1981;Mall et al, 2006). During the southwest (summer) monsoon, warm, moist air prevails, and a strong southwesterly wind jet runs diagonally across the Arabian Sea ( Fig.…”
Section: Introductionmentioning
confidence: 99%
“…These factors are then used to model future yields under temperature and greenhouse gas thresholds. This study assumes crop-specific average percentage yield changes based on the range of studies reported in the meta-analysis review of Mall et al (2006). Such studies comprise of a combination of field-based observations and future climate modeling scenario results.…”
Section: Projected 2050 Deficiencies Under Business-as-usual (Bau) Comentioning
confidence: 99%
“…Observations indicate the agricultural sectorÂŽs vulnerability to changes in monsoon precipitation: with a 19-percent decline in summer monsoon rainfall in 2002, Indian food grain production was reduced by 10-15 percent compared to the previous decadal average (Mall et al 2006). Without adequate water storage facilities, the potential increase of peak monsoon river flow would not be usable for agricultural productivity; increased peak flow may also cause damage to farmland due to river flooding (Gornall et al 2010).…”
Section: Water Constraintsmentioning
confidence: 99%